A novel molecular dynamics approach to simulate micromechanical behavior in characteristic crystallographic planes of transparent alumina ceramics - Jiajun Chen; Meiqing Guo; Shaoying Zhang; Xinyue Wang; Xingming Zhu; Zhenhua Song; Zhiqiang Li (Journal of Materials Research and Technology)
To investigate the anisotropic properties of brittle-prone transparent alumina ceramics (TACs) and guide the optimized design of material modification, this study employed a novel molecular dynamics (MD) approach to reproduce and analyze the anisotropic micromechanical behaviors of TACs during nanoindentation experiments, with a focus on industrially prevalent A-plane {11 2‾ 0} and C-plane (0001) configurations (denoted as TACs-A and TACs-C, respectively). Nanoindentation experiments and morphological observations revealed distinct failure mechanisms: TACs-C exhibited preferential plastic failure characteristics (i.e., displacement pop-in events) during early indentation stages, whereas TACs-A demonstrated intense plasticity-dominated failure in mid-to-late stages due to superior hardness and elastic modulus, ultimately forming radial-intercrossed crack networks. The MD model incorporating the Embedded Atom Method (EAM) potential successfully replicated experimental phenomena. Critical findings include an HCP-to-FCC phase transformation of O atoms in TACs-A during indentation, dominated by Shockley 1/6<112> and Hirth 1/3<100> dislocations that impede slip motion, thereby enhancing mechanical properties and contributing to higher hardness/elastic modulus. Concurrently, dislocation analysis elucidated the early-stage displacement pop-in events in TACs-C: rapid dislocation proliferation (0–5 Å penetration depth) induced localized stress concentration and abrupt displacement. Finally, two optimization strategies (doping modification and graphene atomic coating) were proposed, providing computational modeling support for TACs material design.